Passions in Stoicism - Gagin, François Gabriel Antoine (Estudios de Filosofía, 2006)
After a few general considerations on what the Greek experience of passion represents, the position of Plato and Arisitotle is cansidered to further underline in a contrapunctual manner, the originality of Stoic Psichology which, doing without the presence of the irrationality inherent to the human soul, defines a Passion as a result of an error in judgement. These sicknesses of the soul which, in a stoical perspective, are the passions, reveal an incomprehension and a disagreement of man with his surrounding, and is incapable of living in the present. The physical discourse, propaedeutical of Ethics, is revealing of fhe virtous conduct free of passions.